System justification moderates the relation between hostile (but not benevolent) sexism in the workplace and state anxiety: An experimental study. Issue 4 (4th July 2019) - Pacilli, Maria Giuseppina; Spaccatini, Federica; Giovannelli, Ilaria; Centrone, Delia; Roccato, Michele
ABSTRACT: In an experimental vignette study performed with 92 Portuguese women, we analyzed the relations between exposure to hostile sexism (HS) and benevolent sexism (BS) in a workplace context, system justification (SJ), and anxiety, measured after participants were exposed to an HS, a BS, or a neutral communication about the context of the industry they would have worked in, if selected. The results indicated that both HS and BS fostered participants' anxiety, and that SJ moderated the relation between HS and anxiety. Anxiety was highest among participants low in SJ. Main contributions of the study, limitations, and possible future research directions are discussed.